(untitled) (UCC Law Journal, 2024)
Corporate Governance involves how companies are controlled and the role directors play in running the affairs of companies. Directors owe a fiduciary duty to the companies they administer and are required to observe the utmost good faith in their dealings. Where a director breaches the duties imposed by law or exceeds the powers so conferred, the director is to be personally liable for the damages caused actionable through fiduciary-duty litigation. This paper argues that though directors owe a duty of care, the “business judgment rule” or “business judgment presumption” should serve as a basis to shield directors from liability in cases where the directors are reasonably informed and not self-interested in the making of the business decision. The paper discovers that, unlike other jurisdictions, the Companies Act of Ghana does not codify the business judgment rule. This paper contends that codifying the business judgment rule in Ghana would strike a workable balance between the role of a director in exercising independent and unrestrained judgment on one hand, whilst also exacting accountability on the other hand, to safeguard the interests of the stakeholders of the company. As a way of developing a thesis upon which director conduct and compliance could be measured, this paper recommends that practical guidelines of best practice for directors should be formulated by the courts using the National Corporate Governance Code (National Code) developed by the Institute of Directors of Ghana as a guide. This is significant because, in order to achieve economic efficiency of companies, it is imperative to not hold directors liable for every business decision they make